2007
DOI: 10.1083/jcb.200704166
|View full text |Cite
|
Sign up to set email alerts
|

Two regulatory steps of ER-stress sensor Ire1 involving its cluster formation and interaction with unfolded proteins

Abstract: Chaperone protein BiP binds to Ire1 and dissociates in response to endoplasmic reticulum (ER) stress. However, it remains unclear how the signal transducer Ire1 senses ER stress and is subsequently activated. The crystal structure of the core stress-sensing region (CSSR) of yeast Ire1 luminal domain led to the controversial suggestion that the molecule can bind to unfolded proteins. We demonstrate that, upon ER stress, Ire1 clusters and actually interacts with unfolded proteins. Ire1 mutations that affect thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
342
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 282 publications
(365 citation statements)
references
References 36 publications
16
342
3
4
Order By: Relevance
“…Given that cellular clustering can be a consequence of protein self‐association (Kimata et al , 2007; Li et al , 2010), we next asked whether SPOP self‐association influences its ability to localize to nuclear speckles. Mutations that disrupt SPOP oligomerization through the BTB (Zhuang et al , 2009) and BACK domain (van Geersdaele et al , 2013) have been previously described.…”
Section: Resultsmentioning
confidence: 99%
“…Given that cellular clustering can be a consequence of protein self‐association (Kimata et al , 2007; Li et al , 2010), we next asked whether SPOP self‐association influences its ability to localize to nuclear speckles. Mutations that disrupt SPOP oligomerization through the BTB (Zhuang et al , 2009) and BACK domain (van Geersdaele et al , 2013) have been previously described.…”
Section: Resultsmentioning
confidence: 99%
“…The triggers for this release are unclear. Structural studies of IRE1, which is also controlled by BiP, have posited direct recognition of misfolded proteins that induces a conformation change to the active state (9,10). Whether ATF6 is triggered by a similar mechanism of misfolded protein binding is unclear.…”
mentioning
confidence: 99%
“…Several lines of evidences have suggested that Rot1 is involved in protein folding: ROT1 genetically interacts with genes encoding ER chaperones such as BiP/Kar2, and the unfolded protein response (Kimata et al, 2007;Kohno 2007) was induced in the temperature-sensitive rot1-2 mutant. Furthermore, folding of disulfide-reduced carboxypeptidaseY (CPY) was likely to be severely perturbed in kar2-1 rot1-2 double mutant cells (Takeuchi et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%